“Sometimes you have knowledge but lack the equipment to save a life”: perspectives on health system barriers to post-abortion care in Liberia and Sierra Leone - Vallery Auma Obure; Kenneth Juma; Sherine Athero; Vekeh Donzo; Neneh Conteh-Khali; Ramatou Ouedraogo; Boniface Ayanbekongshie Ushie (Archives of Public Health, 2024)
Abstract Background Abortion is largely restricted in Liberia and Sierra Leone, with exceptions under limited conditions. Consequently, women and girls seeking induced abortion care in these settings resort to unsafe methods, resulting in severe complications. Post-abortion care (PAC) is a lifesaving obstetric intervention to address abortion-related complications, but access to quality and comprehensive PAC in health facilities is daunting. Research on barriers to PAC, drawing on perspectives from diverse stakeholders, is critical to inform specific programmatic improvements to enhance access to quality PAC services. Objectives This study explored stakeholders’ perspectives on the barriers to quality PAC across health facilities in Liberia and Sierra Leone. Methods This cross-sectional qualitative study targeted PAC providers in selected health facilities and policy actors in Liberia and Sierra Leone. We conducted in-depth interviews with 33 healthcare providers – 8 in Liberia and 25 in Sierra Leone; and 13 policy actors – 8 in Liberia and 5 in Sierra Leone. The policy actors included representatives from religious institutions, ministries of health, civil society organizations, and non-government organizations working on sexual and reproductive health (SRH) issues. Audio files of the interviews were transcribed verbatim in the original language of the interview and translated into English by expert translators. A deductive and inductive approach was used to develop a codebook to code the interviews in Dedoose software. Data analysis was conducted using the thematic approach. Findings Diverse viewpoints of what constitutes quality PAC existed among stakeholders in Sierra Leone and Liberia, and these variations are reflected in their practices and behavior around PAC services. Our analysis revealed some weaknesses and gaps in PAC delivery, including a lack of trained providers, which was more pronounced in Sierra Leone than in Liberia. In both countries, the absence of functional PAC equipment, inadequate PAC supplies, and infrastructure-related challenges (e.g., lack of rooms with audio-visual privacy during PAC service) were commonly cited. Limited audio-visual privacy complicated provider-patient interactions, with providers mentioning that this makes patients withhold vital information during history-taking. Providers had no or limited knowledge of the law, and best practices around PAC, leading to delays, denial of services, overcharging fees, and stigmatization of some patients. Conclusion Despite existing policies and interventions on post-abortion, many health facilities in Liberia and Sierra Leone lack essential post-abortion care equipment and supplies and trained providers. There is a need to recruit and train willing providers, along with a clear referral system. Further, sensitizing health providers, stakeholders, and communities on abortion-related policies, guidelines, and value clarification could help improve post-abortion care service provision and uptake.